ANALISIS PERBEDAAN PELAYANAN KESEHATAN PADA PASIEN BPJS DAN PASIEN UMUM (NON-BPJS) - Kurniawan, Yudo; Pujianto, Agung; Andayani, Sri (Jurnal Dinamika Administrasi Bisnis, 2015)
BPJS is one of program from the Indonesiaâ€™s government. This program is held to improve the health of Indonesian citizens by health insurance for people by paying certain fee. Therefore, this study is aimed to determine whether there is difference in quality service provided to the general patient (without BPJS) and the patient with BPJS. This research focus on services in Hospital of Dr. Mohamad Soewandhie in Surabaya with a sample of 65 patients in the outpatient care unit, as it for public patients (non-BPJS) as well as for patients with BPJS program. Data were collected by distributing questionnaires measured with Likert scale. Data analysis technique is independent sample test using SPSS for Windows. The results showed that in all dimensions of service quality, namely tangibles, reliabilities, Responsiveness, Assurance, and Empathy, has an average total score differently on each patient and the patient's non-BPJS BPJS. These results are also supported by statistical calculations where tstatictic for all dimensions of service quality, such as tangibles, reliabilities, responsiveness, assurance, and empathy, have significant level (p)Â  above 0.05.Keywords:quality of service, BPJS, different test